Teaching English Speaking Skill from Traditional Arabic Teaching Adaptation at Pesantren - Tjendani, Endah Nur; Afandi, Rizal (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2023)
This research aims to explore the traditional of teaching language of Kitab in Pesantren, especially at EAL adapted to English speaking class. To gain the purposes, the methods of this research has applied descriptive qualitative research design for gaining a phenomenon, a process, or a specific point of view from the viewpoint of people involved in the process of adaptation model. In depth-observation of preparation document, teaching learning activities and the evaluation system had been done for getting the accuracy data, the data analyzed by Flow Model. It was found that there were clasified into 1) the preparation is written on dailly, weekly, monthly, and anual program, but no lesson plan, 2) teaching materials were aranged into 2 clasical books; grammar book adapted from Ilmu Alat book, and content book related to topic, story, news, ect.for having speaking activities, 3) speaking activities done by in-or-outside class and with-or-without teacher, reading aloud uttered by using rhymn as Sholawatan, learners centered by using setoran, sawir, etc. individually or classically, 4) test and non-test system applied at speaking evaluation. It may conclude that traditional Arabic teaching had been adapted to English speaking skills.